2012
DOI: 10.1371/journal.pone.0040008
|View full text |Cite
|
Sign up to set email alerts
|

Lin28 Mediates Paclitaxel Resistance by Modulating p21, Rb and Let-7a miRNA in Breast Cancer Cells

Abstract: Resistance to chemotherapy is a major obstacle for the effective treatment of cancers. Lin28 has been shown to contribute to tumor relapse after chemotherapy; however, the relationship between Lin28 and chemoresistance remained unknown. In this study, we investigated the association of Lin28 with paclitaxel resistance and identified the underlying mechanisms of action of Lin28 in human breast cancer cell lines and tumor tissues. We found that the expression level of Lin28 was closely associated with the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 19 publications
1
47
0
Order By: Relevance
“…Accordingly, therapeutics such as shRNAs, siRNAs, and chemical compounds that downregulate LIN28A or LIN28B expression or functional activity are unlikely to have harmful side effects in patients. As mentioned earlier, there is already evidence that downregulation of LIN28A in chemotherapy and radiation-resistant breast cancer cells enhanced their sensitivity to the treatments (Lv et al, 2012; Wang et al, 2013). Suppression of LIN28A by shRNA in human glioblastoma cells caused cell cycle arrest in the G1 phase, enhanced apoptosis, and delayed cell proliferation (Qin et al, 2014).…”
Section: The Lin28ab/let-7 Pathway As a Molecular Target For Novel Anmentioning
confidence: 83%
See 1 more Smart Citation
“…Accordingly, therapeutics such as shRNAs, siRNAs, and chemical compounds that downregulate LIN28A or LIN28B expression or functional activity are unlikely to have harmful side effects in patients. As mentioned earlier, there is already evidence that downregulation of LIN28A in chemotherapy and radiation-resistant breast cancer cells enhanced their sensitivity to the treatments (Lv et al, 2012; Wang et al, 2013). Suppression of LIN28A by shRNA in human glioblastoma cells caused cell cycle arrest in the G1 phase, enhanced apoptosis, and delayed cell proliferation (Qin et al, 2014).…”
Section: The Lin28ab/let-7 Pathway As a Molecular Target For Novel Anmentioning
confidence: 83%
“…However, many patients develop metastasis and/or tumor relapse after 6–10 months (Seo et al, 2007). Lin28 was found to mediate resistance of breast cancer cells to paclitaxel by modulating p21, Rb, and Let-7a miRNAs (Lv et al, 2012). As compared to cells expressing a low level of LIN28A, T47D cancer cells with high expression of Lin28 was shown to be more resistant to paclitaxel.…”
Section: Lin28a/lin28b In Cscs Metastasis and Resistance To Chemothmentioning
confidence: 99%
“…Overexpression of LIN28 is known to promote cancer cell proliferation by inhibiting the biogenesis of microRNA let-7 [37,60]. Furthermore, LIN28 overexpression was shown to be correlated with poor prognosis in patients with primary breast tumors [17,32]. Decreased let-7 expression has been linked to increased tumorigenicity and poor patient prognosis in breast as well as many other cancers [12,20,40,59].…”
Section: Introductionmentioning
confidence: 99%
“…LIN28 is expressed in breast cancer tumors, and recent studies have shown that LIN28 is a powerful predictor of poor prognoses and patient clinical outcomes (8,28,29). With this in mind, we were interested in identifying novel LIN28 mRNA targets that could provide insights into the function of LIN28 in breast cancer.…”
mentioning
confidence: 99%